The Effect of Project Based Learning (PJBL) and Inquiry Learning Models on Learning Outcomes of IPAS on the Material of Changes in the Form of Substances in Grade IV Students of SD Negeri 007 Tebing - Munawarah, Hurul; Meilina, Fitria; Khairiyah, Karunia Yulinda (Indonesian Journal of Primary Education, 2024)
This study aims to determine the effect of using Project Based Learning (PjBL) and Inquiry Learning models on learning outcomes. The research used is quantitative research with experimental methods. The design in this study uses a Quasi Experimental design with the form of Nonequivalent Control Group Design. The location of this research is at SD Negeri 007 Tebing. The sampling technique in this study is total sampling where all members of the population are used as research samples, so the sample in this study amounted to 33 fourth grade students of SD Negeri 007 Tebing. The data source used is primary data, namely the researcher went directly to collect data. Data collection techniques in this study are: observation, interviews, documentation, and tests. The research instrument used is a test instrument with a data analysis technique in the form of a t-test. Based on data analysis, the results of the study showed that: 1) There is an effect of using the Project Based Learning (PjBL) learning model on the learning outcomes of science in the material of changes in the state of matter in fourth grade students of SD Negeri 007 Tebing, with t count 6.97 t table 2.080. 2) There is an influence of the use of the Inquiry Learning model on the learning outcomes of science in the material of changes in the state of matter in grade IV students of SD Negeri 007 Tebing, with t count 4.00 t table 2.228. 3) There is a significant difference in the influence of the use of the Project Based Learning (PjBL) and Inquiry Learning models on the learning outcomes of science in the material of changes in the state of matter in grade IV students of SD Negeri 007 Tebing, with t count 2.564 t table 2.040.